Best practices in literacy instruction (Guilford Press, 2003)
Leading researchers and practitioners review the latest findings on key areas of instruction and translate the research into easy-to-implement teaching strategies and ideas. Including updated coverage of early literacy, phonics, comprehension, assessment, adolescent literacy, and more, the second edition also features essential new chapters on vocabulary and fluency instruction.